FUSION OF THE 6Li +58Ni SYSTEM AT SUB-BARRIER ENERGIES (2015)
A fusion excitation function for the 6Li +58Ni system was measured at energies near and below the Coulomb barrier. We describe the procedure used to deduce the fusion cross sections from the angular distributions measured for the protons evaporated from the compound nucleus, by using the proton multiplicity predicted by the code PACE2. The comparison of our results with those reported for a very similar system, 6Li +59Co, in reduced units, shows a very good agreement.